Cathodic mass transfer relationship of carbonic acid solutions with trace dissolved oxygen contamination. Paper number 2731 - John, Doug; Kinsella, Brian; Bailey, Stuart; De Marco, Roland (NACE International, 2008)
Cathodic polarisation curves of carbon steel in carbonic acid solutions typically exhibit alimiting current behaviour that has been associated with the rate of mass transfer. In studiesusing the jet impingement technique, the magnitude of this limiting current behaviour hasbeen found to be strongly affected by the presence of trace dissolved oxygen. This paperpresents a theoretical assessment of the mass transfer limited cathodic current to illustratethe pronounced effect of dissolved oxygen contamination <12 ppb. Discussion is presentedregarding the implications of dissolved oxygen contamination on the interpretation of themechanism of carbon dioxide corrosion.